Editor's choice: role of antiplatelet therapy in patients managed for complex aortic aneurysms using fenestrated or branched endovascular repair - Nana, Petroula; Spanos, Konstantinos; Tsilimparis, Nikolaos; Haulon, Stéphan; Sobocinski, Jonathan; Gallitto, Enrico; Dias, Nuno; Eilenberg, Wolf; Wanhainen, Anders; Mani, Kevin; Böckler, Dittmar; Bertoglio, Luca; et al. (European journal of vascular and endovascular surgery, 2025)
Objective - Despite the increasing number of fenestrated and branched endovascular aortic repair (F/B-EVAR) procedures, evidence on post-operative antiplatelet therapy is very limited. This study aimed to investigate the role of single antiplatelet therapy (SAPT) vs. double antiplatelet therapy (DAPT) after F/B-EVAR in 30 day and follow up outcomes. - Methods - A multicentre retrospective analysis was conducted, including F/B-EVAR patients managed from 1 January 2018 to 31 December 2022. Comparative outcomes were assessed according to post-operative antiplatelet therapy. The cohort was divided into the SAPT group (acetylsalicylic acid [ASA] or clopidogrel) and DAPT group (ASA and clopidogrel). The duration of SAPT or DAPT was one to six months. Primary outcomes were 30 day death, and cardiovascular ischaemic and major haemorrhagic events. Secondary outcomes were survival and target vessel (TV) patency during follow up. - Results - A total of 1 430 patients were included: 955 under SAPT and 475 under DAPT. The 30 day mortality rate was similar (SAPT 2.1% vs. DAPT 1.5%; p = .42). Cardiovascular ischaemic events were lower in the DAPT group (SAPT 11.9% vs. DAPT 8.2%; p = .040), with DAPT being an independent protector for acute mesenteric (p = .009) and lower limb ischaemia (p = .020). No difference was found in 30 day major haemorrhagic events (SAPT 7.5% vs. DAPT 6.3%; p = .40). The mean follow up was 21.8 ± 2.9 months. Cox regression showed no survival confounders, with similar rates between groups (log rank p = .71). DAPT patients enjoyed higher TV patency (SAPT 93.4%, standard error [SE] 0.7% vs. DAPT 97.0%, SE 0.6%; log rank p = .007) at thirty six months. Cox regression revealed B-EVAR as a predictor of worse TV patency (hazard ratio 2.03, 95% confidence interval 1.36 - 3.03; p < .001). DAPT was related to higher patency within B-EVAR patients (SAPT 87.2%, SE 2.1% vs. DAPT 94.9%, SE 1.9%; p < .001). - Conclusion - DAPT after F/B-EVAR was associated with lower risk of cardiovascular ischaemic events and higher TV patency, especially in B-EVAR cases. No difference in major haemorrhagic events was observed at 30 days.
Online verfügbar 24 September 2024, Version des Artikels 8 February 2025
Gesehen am 25.09.2025